The dynamic heart in daily life : connecting Christ to human experience - Pierre, Jeremy, 1979- (Greensboro, NC : New Growth Press, 2016)
Our approach to counseling and personal ministry is often lopsided--we treat people as minds to be taught or problems to be fixed, moving too quickly toward applying biblical solutions without taking the time to love people well and understand their experiences and hurts. The Dynamic Heart in Daily Life provides a comprehensive view of how the heart works and how Christ redeems it. Pierre's faith-centered understanding of people combines with a Word-centered methodology to give readers a practical way to help others better understand their tough experiences and who they are in light of who Jesus is. Pierre guides readers through four key activities -- reading, reflecting, relating, and renewing -- that will consistently position them to understand everyday human experiences in light of Scripture. Pierre exposes the false dichotomy between the spiritual and seemingly unspiritual parts of the human experience, showing how every thought, feeling, and choice actually expresses the spiritual activity of the heart. He shows how faith in Christ is the means by which the heart begins to respond differently. Faith is not only the entry point for heart change, but also an expression of our everyday, ongoing need for Christ. Pierre's holistic view of counseling -- forged by his experiences as a counselor, pastor, and seminary professor -- equips readers to understand how everyday beliefs, desires, and commitments shape how we respond to life's biggest struggles and how an active relationship of trust in God is the foundation for lifelong change. - Publisher
Includes bibliographical references
Keywords: Change (Psychology) -- Religious aspects -- Christianity; Christianity -- Psychology; Experience (Religion); Pastoral counseling